Bail-Out Pull-Through Pull-Back Technique for Accidental Coverage of the Left Common Carotid Artery During Thoracic Endovascular Aortic Repair. (April 2022) - Okamura, Homare; Arakawa, Mamoru; Kitada, Yuichiro; Miyagawa, Atsushi; Adachi, Hideo
Purpose: We describe a pull-through pull-back technique to revascularize the left common carotid artery (LCCA) that was unintentionally covered during thoracic endovascular aortic repair (TEVAR). Case Report: A 69-year-old man presented with back pain secondary to acute type B aortic dissection with an intimal tear in the proximal descending aorta. Serial computed tomography (CT) revealed an enlarged descending aorta and proximal progression of the aortic dissection. He underwent left carotid-subclavian artery bypass and TEVAR, 10 days after admission. The Valiant Navion stent graft without a bare stent was deployed proximally; however, the LCCA was unintentionally covered by the stent graft during this procedure. A pull-through form was created between the left axillary and femoral arteries using a 0.035-inch guide wire. The pull-through guide wire was gently pulled, and the greater curvature of the proximal end of the stent graft was displaced distally. Angiography confirmed restoration of antegrade blood flow into the LCCA. The patient's postoperative course was uneventful. Follow-up CT performed 6 months postoperatively confirmed preserved blood flow into the LCCA without endoleak nor stent migration. Conclusion: The pull-through pull-back technique is a feasible troubleshooting strategy for accidental coverage of supra-aortic vessels during TEVAR.